Analisis Prosedur Perhitungan, Pemotongan Penyetoran dan Pelaporan PPH Final Pasal 4 Ayat (2) Atas Perkerjaan Jasa Kontruksi PT. Telkom Akses - Ferdi Ramadi Pamungkas Priambono; Arief Satriansyah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The research was motivated by the fact that there were still errors in input in the application system tax resulting from miscalculation of PPh 4(2) at PT. Telkom Access the results of Fiscal Year observations 2023. The research objectives are 1) to find out the procedures for calculating, cutting, deposit, and reporting of Final Income Tax Article 4 (2) for PT construction services work. Telkom Access. 2) to find out whether there are differences in procedures implemented by PT.Telkom Access the provisions of tax regulations related to Final Income Tax Article 4 (2) above construction services work. This type of quantitative research uses descriptive analysis techniques. The population and research sample is PPh 4(2) transaction data for the 2023 Tax Year at PT. Telkom Access. The research results show that 1) Calculation procedures, deductions, payments and Final PPh 4(2) reporting implemented at PT. Telkom Access includes a) Process calculations and deductions; b) Reconciliation Process; c) Deposit/Payment Process; d) Process Reporting. 2) There are no significant differences regarding calculation procedures, deductions, deposit, and reporting of Final Income Tax 4 (2) for PT construction services work. Telkom Access with provisions of Final Income Tax regulations Article 4 (2) for construction services work. This means everything the procedure is in accordance with the regulations.